THE ROLE OF FAMILY IN DEVELOPING EARLY CHILDHOOD POTENSIAL - Budiyono Budiyono (PSGA LP2M IAIN Pontianak, 2020)
This study aims to examine the role of parents in developing children’s potential and indentify various problems faced. Parents are not only the instrument in developing children’s potential, but their presence as a place of first learning contributes to influence other factors such as schoold and the environment. By special study with descriptive qualitative research types, and strengthened by revelant literature to answer or confirm the research findings. The result of study indicate the stage of children’s education should be carried out in the womb up to six years old. Each child’s potential for development respectively, careful in understanding of the child’s potential will determine accuracy in facilitating their needs. Millenial era is a challange for parents in controlling child’s will especially in using gadget, as anticipation not having a bad impact but also doesn’t deny the great benefit.